SISTEM PENDUKUNG KEPUTUSAN CALON PENERIMA BEASISWA KURANG MAMPU PADA SMK SULTAN AGUNG 1 MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Fikandda, Johan; Rahman Prehanto, Dedy; Yuli Setyawan, Aditya (Inovate, 2019)
Scholarship of underprivileged is a grant provided by goverment or institutions to students fromunderprivileged family. Scholarship covering all levels of education, whether student still in primary schooluntil college. The selection of scholarship is obtained if students meet the specified criteria. Scholarshipselection in the SMK Sultan Agung 1 Jombang sometimes not accordance with assessment results. Manyrich student are able to get scholarship while underprivileged students don’t get scholarship. The largenumber of students applying for scholarship make it difficult to make a decision. Based on this, build adecision support system can assist SMK Sultan Agung 1 Jombang to manage the selection of scholarshipbased on criteria. Decision Support System are build using PHP as programming language and MySQL asdatabase. This system is called Simple Additive Weighting (SAW). SAW method is performing a weightedsum of performance ratings on each alternative on all attributes. This method are suitable to be used inmaking decision support system because the result obtained accordingly. The System do ranking from thebest alternative of the student who applied scholarship. System has been tested to determine performanceof the system along with functions contained in the system. Testing is done using Blackbox testing method.This test done by trying the existing function on the system, whether it is suitable with the expected resultby the school. The result obtained from Blackbox testing indicate that the system created has been runningwell.Keyword : Decision Support System, Simple Additive Weighting, Scholarship